Rancang Bangun Sistem Peminjaman Kendaraan Dinas Berbasis Web Studi Kasus pada Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri (BBSPJPPI) Kota Semarang - Trisya Aprilia; Migunani Migunani; Maya Utami Dewi; Khoirur Rozikin; Nuris Dwi Setiawan (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
Official vehicles are crucial assets in ensuring the effectiveness and efficiency of government institutions. However, manual borrowing systems often cause problems such as inaccurate records, overlapping schedules, tracking difficulties, and limited transparency. Similar issues occur at the Industrial Pollution Prevention Standardization and Service Center (BBSPJPPI) Semarang, which still relies on Google Forms for vehicle borrowing, leading to suboptimal monitoring and weak data integration. This study develops a web-based vehicle borrowing information system using the Research and Development (R&D) method. The system provides integrated features including schedule management, vehicle availability tracking, borrower information, and usage history. The implementation of this system is expected to improve administrative efficiency, enhance data accuracy, and strengthen transparency in asset management, thereby enabling institutional operations to run more effectively, accountably, and in a more organized manner.